Co-optima fuels combustion: A comprehensive experimental investigation of prenol isomers. (15th October 2019) - Ninnemann, Erik; Kim, Gihun; Laich, Andrew; Almansour, Bader; Terracciano, Anthony C.; Park, Suhyeon; Thurmond, Kyle; Neupane, Sneha; Wagnon, Scott; Pitz, William J.; Vasu, Subith S.
Abstract: Carbon monoxide time-histories, ignition delay times, and laminar burning velocity measurements are reported for the oxidation of 3-methyl-2-buten-1-ol (prenol) and 3-methyl-3-buten-1-ol (isoprenol). These prenols are fuel candidates outlined by the U.S. Department of Energy's Co-Optimization of Fuels and Engines (Co-Optima) program. The laminar burning velocity measurements were conducted for two fuels with synthetic air within a constant-volume spherical combustion chamber at initial conditions of 428 K and 1 atm for a range of equivalence ratios from 0.75 to 1.50. The laminar burning velocities of the two fuels were found to be similar, and the maximum value occurred at an equivalence ratio near 1.0. Carbon monoxide time-histories and ignition delay times were recorded behind reflected shockwaves in a double-diaphragm, heated shock tube over the temperature range 1269–1472 K near 9.4 atm with a mixture of 0.05% fuel/0.35% O2 /99.6% Ar. Comparisons with predictions of a detailed chemical kinetic mechanism from the literature were provided. Current model predictions overpredicted both the ignition delay time and the max CO yield; however, the model captured the profile of CO formation well. Detailed uncertainty and sensitivity analyses were carried out to identify important reactions that need attention for accurate prediction of these fuel's chemistry. Further investigation into the rate of C3 H3  + O2  = CH2 CO + HCO reaction was suggested based on current experiments. The experimental data and analysis presented here is critical in the development, validation and improvement of kinetic models of these promising Co-Optima fuels.